Effectiveness of early warning systems in the detection of infectious diseases outbreaks: a systematic review - Meckawy, Rehab; Stuckler, David; Mehta, Adityavarman; Al-Ahdal, Tareq; Doebbeling, Bradley N. (BMC public health, 2022)
Global pandemics have occurred with increasing frequency over the past decade reflecting the sub-optimum operationalization of surveillance systems handling human health data. Despite the wide array of current surveillance methods, their effectiveness varies with multiple factors. Here, we perform a systematic review of the effectiveness of alternative infectious diseases Early Warning Systems (EWSs) with a focus on the surveillance data collection methods, and taking into consideration feasibility in different settings.
Gesehen am 17.01.2023